Bibliometric Analysis of the Management School Principals and the Improvement of Teacher Pedagogy in the Digital Era based on the Scopus Database (1966-2024) - Sutrisno, Shidiq Agung; Sumardjoko, Bambang; Anshori, Ari; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to identify development mapping and research directions on the Islamic ecosystem in publications listed on the Scopus index. The approach used in this research is bibliometric analysis, which is used to explore all publications indexed in the Scopus database related to "Management And Pedagogy" from 1966 to 2024. The data analyzed was processed using Excel and R/R-Studio software. To analyze the occurrence patterns of keywords and document citations simultaneously, this research uses the VOSviewer visual analysis tool. The research results showed that 2663 publications were relevant to the criteria and focus set by the researchers. The main finding of this research is that there is an annual growth of 6.1%, and the peak of publications on "Management And Pedagogy" occurs in 2023. Monash University was identified as the main contributor with an affiliation of 25 documents. A researcher named Alison Ja has the highest productivity in the topic "Management And Pedagogy". However, it is important to note that this bibliometric analysis is based only on data from Scopus, while other national and international data sources are not included in the analysis. Therefore, this study provides a comprehensive overview of the literature that is accessible to researchers interested in the field of "Management And Pedagogy" and also provides suggestions for future research directions.